INTERNALIZATION OF ISLAMIC VALUES IN THE 21st CENTURY CONSTRUCTION ORNAMENTS - Olivia de H. Basoeki; Wu Mingchang (Religio Education, 2021)
This article aims to determine the concepts as well as some Islamic construction ornaments that contain Islamic values. Art and spirituality will not be complete if they do not touch on architecture, so Islamic architecture has an important meaning from the perspective of spirituality. In the 21st century, there are architectural issues in how buildings respond to the environment. Therefore, buildings including ornaments must be environmentally friendly and apply the concept of simplicity design and apply appropriate technology. The research used is library research with descriptive methods. The result of this research is that the art of decoration is one of the most important character building elements in Islamic architecture. Types of typical Middle Eastern ornaments include calligraphy, geometric ornaments, and arabesk.